2012
DOI: 10.1007/s12020-012-9849-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protein oxidation and its association with lipid peroxidation and thyrotropin levels in overt and subclinical hypothyroidism

Abstract: Both overt (OHT) and subclinical hypothyroid (SHT) disorders have been found to be associated with increased oxidative stress (OXS). Excess thyrotropin [thyroid stimulating hormone (TSH)] is known to directly produce OXS. Increased lipid peroxidation is known to facilitate protein carbonylation. However, the associations between lipid and protein oxidation and elevated TSH levels have not been studied. Thyroid profile, lipid peroxidation as malondialdehyde (MDA) levels and protein carbonylation as protein carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 22 publications
8
41
0
Order By: Relevance
“…Our findings are well in support of previous reports showing increase in lipid and protein oxidation in OHT patients compared to controls [1,3]. An increase MDA level has been reported earlier in OHT [1,3,15] and SHT patients [2,15]. Our observation of increased protein oxidation supports the previous studies presenting higher level of PCO in OHT group [1,15,18].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are well in support of previous reports showing increase in lipid and protein oxidation in OHT patients compared to controls [1,3]. An increase MDA level has been reported earlier in OHT [1,3,15] and SHT patients [2,15]. Our observation of increased protein oxidation supports the previous studies presenting higher level of PCO in OHT group [1,15,18].…”
Section: Discussionsupporting
confidence: 93%
“…We have previously studied and reported OS in both SHT and OHT by measuring oxidative damage to proteins in the form of protein carbonyls [15] and recorded changes in enzymatic and non-enzymatic antioxidant status in hypothyroidism [16]. Recently, IMA has been reported as an OS marker in hypercholesterolemia [5] and endocrine diseases that include diabetes [13], metabolic syndrome [17], and obesity [18].…”
mentioning
confidence: 99%
“…Our finding of high MDA level in OHT group compared to SHT group indicate that oxidative damage increases with increased severity of hypothyroidism.Moreover, serum MDA levels showed significantly positive correlation with TC, TGs, LDL and TSH serum levels and a significant negative correlation with HDL, free T3 and free T4 serum levels.Our results areconsistent with several studieswhich demonstrated that MDA levels were significantly elevated in OHT [3, 21, 34, 36 -39] as well as in SHT [3,21,34,37,40] patients compared with euthyroid controls which may be an indirect suggestion of increased oxidative stress in these pathological states.In addition, some of the previous studies found a significant correlation between TSH and MDA which was lost after nullifying the effects of each of the coronary lipid risk factors among hypothyroid subjects and suggested that the increase in MDA was not associated with thyroid hormones but was related to elevated plasma lipids [38,39].…”
Section: Discussion:-supporting
confidence: 93%
“…It was described that, despite being a hypometabolic state, increased lipid peroxide levels can occur in hypothyroidism due to slower clearance rate [38]. Hyperlipidemia, decreased cholesterol clearance, deficient antioxidant system, effects of thyroid hormones on regulation of antioxidant enzymes and excess TSH are the other proposed mechanisms associated with increased OXS in hypothyroidism [37].…”
Section: Discussion:-mentioning
confidence: 99%
“…5,6 Accordingly, there are data that associate hypothyroid status to enhanced oxidative stress. [7][8][9] However, this issue is far from being completely settled in that, for instance, when hypothyroid rats were treated with 3,3¢,5-triiodothyronine (T3), a significant increase in the level of oxidative stress parameters in the mitochondrial fraction (MF) was recorded in adult rat brain. 10 However, hydrogen peroxide (H 2 O 2 ) content of the MF as well as post-mitochondrial fractions of cerebral cortex was elevated by induced hypothyroidism and reverted to normal level by subsequent treatment of T3.…”
mentioning
confidence: 99%